Engineered small extracellular vesicles as a versatile platform to efficiently load ferulic acid via an “esterase-responsive active loading” strategy - Man, Fulong; Xing, Huaran; Wang, Haoran; Wang, Junfeng; Lu, Rong (Frontiers in Bioengineering and Biotechnology, 2022)
As nano-drug carriers, small extracellular vesicles (sEVs) have shown unique advantages, but their drug loading and encapsulation efficiency are far from being satisfied, especially for the loading of hydrophilic small-molecule drugs. Inspired by the strategies of active loading of liposomal nanomedicines, pre-drug design and immobilization enzyme, here we developed a new platform, named "Esterase-responsive Active Loading" (EAL), for the efficient and stable drug encapsulation of sEVs. Widely used ferulic acid ester derivatives were chosen as prodrugs based on the EAL of engineered sEVs to establish a continuous transmembrane ion gradient for achieving efficient loading of active molecule ferulic acid into sEVs. The EAL showed that the drug loading and encapsulation efficiency were around 6-fold and 5-fold higher than passive loading, respectively. Moreover, characterization by nano-flow cytometry and Malvern particle size analyzer showed that differential ultracentrifugation combined with multiple types of membrane filtration methods can achieve large-scale and high-quality production of sEVs. Finally, extracellular and intracellular assessments further confirmed the superior performance of the EAL-prepared sEVs-loaded ferulic acid preparation in terms of slow release and low toxicity. Taken together, these findings will provide an instructive insight into the development of sEV-based delivery systems.